How do bank capital and capital buffer affect risk: Empirical evidence from large US commercial banks - Faisal Abbas; Zahid Irshad Younas (Journal of Central Banking Theory and Practice, 2021)
This research aims to investigate the influence of bank capital, risk-based capital and bank capital buffers on the behaviour of bank risk-taking by applying GMM on the data of US commercial banks ranges from 2002 to 2018. The findings show that bank capital has a positive influence on total risk. However, risk-based capital and capital buffer have a negative impact on total risk. In addition, the results showed that the relationship between bank asset risk and bank capital, risk-based capital and a capital buffer is negative in pre, amid and post-crisis periods. The findings also reveal that the result of bank capital, risk-based capital and a capital buffer is not similar in case of well, adequately, under, significantly under, and critically undercapitalized banks. Our conclusions have numerous implications for policymakers and regulators in the banking sector.
Keywords: G21; G28; G32; 330; Bank capital; Total Risk-Based Bank capital; Capital Buffers; Total Risk and Asset Risk